Exploring a rare oncologic complication: alveolar rhabdomyosarcoma in HIV patient - Santoso, Dimas; Santoso, Budi; Kristyana, Septian; Candradikusuma, Didi; Natasia, Septalisa; Evatta, Arde (Deka in Medicine, 2024)
BACKGROUND: Alveolar rhabdomyosarcoma is one of the rare oncological complications in Human Immunodeficiency Virus (HIV) patients, but it has a serious impact. Therefore, case report study discussing case of alveolar rhabdomyosarcoma in HIV patient is very important. CASE: A 22-year-old man complained of pain and a growing lump behind his right knee for 9 months. The lump, initially small, became larger and more painful, affecting his ability to move his leg. The patient was diagnosed with HIV 3 years ago and also had leprosy. Additionally, the patient had a history of weight loss and a low body mass index (BMI). Physical examination revealed a 10x15x10 cm mass behind the right knee. Magnetic Resonance Imaging (MRI) of the right knee showed a complex cystic solid lesion involving several muscles and blood vessels. Fine Needle Aspiration Biopsy (FNAB) suggested a High-Grade Sarcoma. Open biopsy confirmed alveolar rhabdomyosarcoma with aggressive features and high mitotic activity. CONCLUSION: In conclusion, our study reported the first case of alveolar rhabdomyosarcoma in an HIV patient. Our study emphasizes the importance of thorough diagnosis for suspected malignancies in HIV patients.